Communication Between Midwives and Pregnant Women in Fluor Albus Education: Qualitative Perspective - Ivana Devitasari; Rena Oki Alestari; Lidia Widia (Health and Technology Journal (HTechJ), 2025)
Fluor albus is a common condition that occurs in pregnant women and can be caused by hormonal changes, infections, or poor hygiene. If not appropriately treated, fluor albus can increase the risk of infection in the reproductive tract, which can affect the health of the mother and fetus. Midwife communication plays an important role in providing practical education to improve the understanding and behavior of pregnant women in dealing with fluor albus. This study aims to analyze the communication between midwives and pregnant women in fluor albus education and identify effective methods in improving the understanding of pregnant women. This study used a qualitative approach with a phenomenological method. Data were collected through in-depth interviews with 10 midwives and 15 pregnant women who had received fluor albus education in antenatal services. Data analysis was carried out using thematic analysis techniques. The results showed that midwife communication methods involving verbal communication, educational media, and direct demonstrations improved the understanding of pregnant women. However, obstacles such as limited consultation time, varying levels of education, and social stigma related to fluor albus are still challenges in educational communication. This study concludes that effective communication between midwives and pregnant women can improve the understanding and behavior of mothers in dealing with fluor albus. Communication training for midwives and the use of digital technology in health education are recommended to increase the effectiveness of information delivery.